Obliterative vaginal procedure for post hysterectomy vault prolapse in severe factor 7 deficiency: a case report and literature review - Jacob, Kirthana Rebecca; Kumari, Minakshi; Kumari, Pushplata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
There is a concern about perioperative bleeding with any surgical intervention in patient with congenital factor VII (FVII) deficiency. The optimum dosage regimen for recombinant activated factor VII (rFVIIa) use has been not clearly established. We report a woman with post hysterectomy vault prolapse management with congenital FVII deficiency who underwent obliterative vaginal procedure. A 50-year-women with congenital FVII deficiency was diagnosed as post hysterectomy vault prolapse and planned for partial colpocleisis. She was planned to monitor FVII activity and prothrombin time international normalized ratio (PT/NR) intraoperatively. At the start of surgery, FVII activity was 3% and PT was INR 35.3 with INR of 2.83. (0.8-1.2). Presuming the improvement of 25% activity, 5 mg (70 mcg/kg body wt.) rFVIIa was administered. The PT was improved to 28.4 sec, Surgery was successfully completed without unexpected bleeding. Post operatively there was no oozing hence FVII activity and PT-INR was not checked. An additional rFVIIa dose of 2mg was given prophylactically after 12 hours of surgery. The patient was discharged on the third day after surgery without postoperative complication. In this case, rFVIIa was used just twice and there were no bleeding events during the perioperative period. Previous reports suggested using 15-30 μg/kg of rFVIIa before surgery and subsequent every 4-6 h in the first 24 h, then increasing the interval to 8-12 h. It is necessary to evaluate optimal dose of rFVIIa based on the risk and surgical invasiveness for each case. Our patient with congenital FVII deficiency uneventfully underwent obliterative vaginal procedure.